Changing incentives to ACCELERATE drug development for paediatric cancer. (16th January 2023) - de Rojas, Teresa; Kearns, Pamela; Blanc, Patricia; Skolnik, Jeffrey; Fox, Elizabeth; Knox, Leona; Rousseau, Raphael; Doz, François; Bird, Nick; Pearson, Andrew J.; Vassal, Gilles
Abstract: Background: More effective incentives are needed to motivate paediatric oncology drug development, uncoupling it from dependency on adult drug development. Although the current European and North‐American legislations aim to promote drug development for paediatrics and rare diseases, children and adolescents with cancer have not benefited as expected from these initiatives and cancer remains the first cause of death by disease in children older than one. Drug development for childhood cancer remains dependent on adult cancer indications and their potential market. The balance between the investment needed to execute a Paediatric Investigation Plan (PIP) in Europe and an initial Paediatric Study Plan (iPSP) in the US, coupled with the potential financial reward has not been sufficiently attractive to incite the pharmaceutical industry to develop drugs for rare indications such as childhood cancer. Methods: We propose changes in the timing and nature of the rewards within the European Paediatric Medicine Regulation (PMR) and Regulation on Orphan Medicinal Products (both currently under review), which would drive earlier initiation of paediatric oncology studies and provide incentives for drug development specifically for childhood indications. Results: We suggest modifying the PMR to ensure mechanism‐of‐action driven mandatory PIP and reorganization of incentives to a stepwise and incremental approach. Interim and final deliverables should be defined within a PIP or iPSP, each attracting a reward on completion. A crucial change would be the introduction of the interim deliverable requiring production of paediatric data that inform the go/no‐go decisions on whether to take a drug forward to paediatric efficacy trials. Conclusion: Additionally, to address the critical gap in the current framework where there is a complete lack of incentives to promote paediatric‐specific cancer drug development, we propose the introduction of early rewards in the Orphan Regulation, with a variant on the US‐Creating Hope Act and its priority review vouchers. Abstract : More effective incentives are needed to motivate paediatric oncology drug development, uncoupling it from dependency on adult drug development. We propose substantial changes in the timing and nature of the rewards within the European Paediatric Medicine Regulation (PMR) and Regulation on Orphan Medicinal Products (both currently under review), which would drive earlier initiation of paediatric oncology studies and provide incentives for drug development specifically for childhood indications. Incentives should be implemented earlier rather than later in the drug development process, and be staged, milestone‐driven, novel, proportional to work completed at each phase and transferrable.